2019
DOI: 10.1159/000501272
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Clinical Imaging Assessment of the Outcome in Mild-to-Moderate Acne: A Prospective Study

Abstract: Background: The quality of outcome assessment in acne studies has been either subjective/insufficient or time consuming through the ordinary lesion counting. Objective: To evaluate the application of multimodal clinical imaging (MCI), a combination of imaging technology and computation, in the assessment of acne lesions in a clinical study setting. Methods: A prospective, monocentric, single-group open study designed to evaluate the efficacy and tolerance of a cosmetic product (IP/SG) in subjects with mild-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The CADI has been used in 13 studies 30,31,[41][42][43][44][45][46][47][48][49][50][51] describing pharmacological topical interventions (Table 2). The studies investigated the use of topical nadifloxacin and benzoyl peroxide, clindamycin and benzoyl peroxide, combined retinaldehyde and glycolic acid cream, adapalene and benzoyl peroxide, erythromycin and zinc acetate and several dermocosmetic products.…”
Section: Topical Drug Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CADI has been used in 13 studies 30,31,[41][42][43][44][45][46][47][48][49][50][51] describing pharmacological topical interventions (Table 2). The studies investigated the use of topical nadifloxacin and benzoyl peroxide, clindamycin and benzoyl peroxide, combined retinaldehyde and glycolic acid cream, adapalene and benzoyl peroxide, erythromycin and zinc acetate and several dermocosmetic products.…”
Section: Topical Drug Interventionsmentioning
confidence: 99%
“…30,31,42,43,[45][46][47][49][50][51] One study 48 reported the percentage improvement and two studies gave a descriptive account of QoL improvement. 41,44 All 14 studies depicted improvement in CADI scores following intervention; however statistical significance was not always reported.…”
Section: Topical Drug Interventionsmentioning
confidence: 99%